2020
DOI: 10.1016/j.vas.2020.100142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of trehalose supplementation on growth performance and intestinal morphology in broiler chickens

Abstract: Highlights Trehalose improved intestinal morphology. Trehalose improved broiler growth performance without antibiotics. Trehalose's effects may depend on feeding conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
(32 reference statements)
0
13
0
1
Order By: Relevance
“…The health and morphology of the intestinal tract of birds are easily affected by the environment and environmental conditions [25]. The present study measured intestinal morphological parameters such as VH, CD and VCR, as they are frequently used as indicators of nutrient absorption and growth performance in hens [26]. A larger VH and VCR in the small intestine as well as a larger VCR in the caecum were observed in the NRS group.…”
Section: Discussionmentioning
confidence: 71%
“…The health and morphology of the intestinal tract of birds are easily affected by the environment and environmental conditions [25]. The present study measured intestinal morphological parameters such as VH, CD and VCR, as they are frequently used as indicators of nutrient absorption and growth performance in hens [26]. A larger VH and VCR in the small intestine as well as a larger VCR in the caecum were observed in the NRS group.…”
Section: Discussionmentioning
confidence: 71%
“…The histomorphometry of duodenum, jejunum, and ileum of the chickens at 21 days of age are presented in Table 4. For a healthy chicken, villus height/crypt depth (VH:CD) ratio is expected to be at least 5 (five parts of villus per one part of crypt) [30], as observed in G1. Epithelial sloughing was observed in non-treated challenged chickens (G2) and treated with blank formulation (LNC, G7).…”
Section: Histomorphometric Measurements Of the Small Intestinementioning
confidence: 99%
“…For this purpose, the formulations were aliquoted in amber glass vials (two for each condition) and kept at room temperature (20 • C) or under refrigeration (8 • C). At different time intervals (1,7,15,30, and 60 days), samples were collected based on two different procedures: one vial was kept at rest while the other was homogenized before pipetting. Afterwards, samples were quantified by HPLC, as previously described.…”
Section: Evaluation Of the Presence Of Nanocrystalsmentioning
confidence: 99%
“…Literature suggests that a greater VH/CD ratio was associated with the broiler's increased capacity to absorb the nutrients deriving from the digestion process (Ruangpanit et al, 2020). In this study, the duodenum and ileum of additive-administrated broilers showed a higher VH ratio to CD than that of control, suggesting that the additive could improve the intestinal function in absorbing the nutrients.…”
Section: Intestinal Morphology Of Broilersmentioning
confidence: 49%